Outcomes of eyes with retinal vein occlusion that are lost to follow-up after antivascular endothelial growth factor therapy. Issue 12 (28th June 2021) - Salabati, Mirataollah; Mahmoudzadeh, Raziyeh; Wong, Jae-Chiang; Patel, Dillan; Patel, Samir N; Obeid, Anthony; Sivalingam, Arunan; Vander, James F; Garg, Sunir J; Ho, Allen C; Regillo, Carl D; Hsu, Jason
Abstract : Background/aims: To evaluate the outcomes of eyes with macular oedema due to retinal vein occlusion (RVO) that are lost to follow-up (LTFU) after antivascular endothelial growth factor (VEGF) injections. Method: A retrospective, single-centre, consecutive case series of RVO patients receiving injections who were LTFU >6 months was conducted. Data were collected from the visit before LTFU; return visit; 3 months, 6 months and 12 months after return; and the final visit. Results: Ninety eyes of 83 patients were included. Fifty (55.5%) eyes had branch RVO and 40 (44.5%) had central RVO. Mean LTFU duration was 277.8 days with additional mean follow-up for 748.1 days after return. Mean logarithm of the minimum angle of resolution visual acuity (VA) (Snellen) at the visit before LTFU was 0.72 (20/105) which worsened on return [1.04 (20/219), p<0.001) and remained worse at all timepoints after return: 0.92 (20/166) at 3 months (p<0.001), 0.97 (20/187) at 6 months (p<0.001), 0.94 (20/174) at 12 months (p<0.001) and 1.01 (20/205) at final visit (p<0.001). Mean central foveal thickness (CFT) increased from 252 µm at the visit before LTFU to 396 µm at the return visit (p<0.001). No difference in CFT was noted by 3 months (258 µm, p=0.71), 6 months (241 µm, p=0.54) or 12 months after return (250 µm, p=0.95). CFT was thinner at the final visit (215 µm, p=0.018). Conclusion: RVO patients receiving anti-VEGF injections who were LTFU experienced a decline in VA that did not return to the levels seen before LTFU despite improvement in CFT after restarting therapy, underscoring the importance of ongoing treatment.